2014
DOI: 10.5296/ijhrs.v4i3.6367
|View full text |Cite
|
Sign up to set email alerts
|

Staff Recruitment and Selection Process in the Nigerian Public Service: What is to be done?

Abstract: The recruitment and selection of staff in any organization be it public or private sector is of paramount importance to the organization. This is so because it is the staff that turns the vision and mission of the organization into reality. Thus, the objectives of any organization can only be realized through the effective co-ordination of the human resource (staff) of the organization. This paper attempts an examination of the process of staff recruitment and selection in the public service of Nigeria. Five r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 4 publications
1
12
0
Order By: Relevance
“…The essence of this process is to make sure that those to be hired meet up with the standard and expectations of the organization. Furthermore, Omisore and Okofu [19] identified two methods of selection: a selection from within the service embracing reassignment and promotion; and selection from outside the service recruitment. However, Ahmad and Schroeder [17] differing slightly in semantics with Omisore and Okofu [19], agreed that there are two methods of recruitment: External and Internal recruitment.…”
Section: Recruitment and Selectionmentioning
confidence: 99%
“…The essence of this process is to make sure that those to be hired meet up with the standard and expectations of the organization. Furthermore, Omisore and Okofu [19] identified two methods of selection: a selection from within the service embracing reassignment and promotion; and selection from outside the service recruitment. However, Ahmad and Schroeder [17] differing slightly in semantics with Omisore and Okofu [19], agreed that there are two methods of recruitment: External and Internal recruitment.…”
Section: Recruitment and Selectionmentioning
confidence: 99%
“…First, it strengthens the bonds that already exist between the employee and the employers since applicants are existing members of the organization. Also, it reduces the cost of hiring and training that is needed for new entrants; eliminates the cost of advertisement in national newspapers since adverts are easily placed on the company's notice board or circulated through internal memo to inform interested applicants of available job vacancies within the organization (Omisore & Okofu, 2014). Internal recruitment provides opportunity for career progression and development, increases employee retention and a strong support for succession planning (CIPD, 2016).…”
Section: Overview Of Human Resources Recruitmentmentioning
confidence: 99%
“…Selection is the process of generating a small pool of people who have the highest probability of success on their job. It has to do with making final decision on the most suitable candidates to fill vacant job positions based on relevant qualifications, experience and aptitude (Naveen & Raju, 2014;Omisore & Okofu, 2014). In today's work place, managers must be extremely careful in the selection of candidates for job positions because the end result of selection may either make or mar the success of an organization.…”
Section: Human Resources Selection Reviewedmentioning
confidence: 99%
See 1 more Smart Citation
“…It is not unusual for some within the civil service to ascribe political meanings and prejudices to government activities, policies and projects based on primordial, religious, ethnic and regional sentiments. The adoption of a quota system for employment and promotion, adherence to the federal-character principle 3 and the government’s constant interference in the operations of the public sector (especially through recurrent alterations in higher positions and infringing on its recruitment processes) revealed that political considerations in place of merit have played a central role in the public institutions (Omisore and Okofu, 2014). It is challenging for strong institutions to emerge when senior officials of these government institutions are appointed on the basis of class affiliation, ethnic cleavages, religion and inter-personal relations, as well as other primordial allegiances (personal communication, 4 July 2014).…”
Section: The Nigerian Public Service: Big Institution Little Productmentioning
confidence: 99%